Putting Barbarians in Their Place - Pearce, Scott (JAOS, 2024)
In this review, we follow Haun Saussy through his The Making of Barbarians, examining how "those within," the people of the traditional Chinese world, developed ideas of "those without," constructing the "barbarian" so as to construct a Self. But the "self," "that within," was itself in an endless process of transformation, as new peoples entered the Chinese world to appropriate its various fineries. And of equal interest: some did not wish to enter at all. The route we will take on this excursion with Saussy is a circuitous one, filled with fascinating insights, along with a few troublesome potholes.